Diseño de una aplicación web y movil e-comerce para la empresa MALIGBBLUE FASHION - Acaro Cañar, Jonathan Leonardo (2021)
The Web has become a platform and an architecture of participation where users can contribute and interact with the content of a Web site to create information or create connection with them, this refers to a type of dynamic web page where the user can generate information. Web 2.0 is the transition from traditional applications with which there would be no interaction in static webs, on the other hand Web 2.0 is the evolution towards applications that work through the web focused on the end user which are applications that generate collaboration and services that replace desktop applications. For this reason we will develop a web and mobile application for the administrative management of the clothing company Maligblue Fashion which provides its services of clothing for women and men nationwide with which they can learn about their new models of each collection, separate their models to purchase them, register your order to send them home or a parcel service to deliver it personally, all this because before the pandemic was done in person with salespeople and visitors in each store with physical samples to each store nationwide and because of this mishap are in the decision to create a website to offer services via the same. Keywords: Web